Fish community structure in Anil River estuary, São Luís Island, Maranhão State. - Júnior, José de Ribamar Pinheiro; de Castro, Antonio Carlos Leal; Gomes, Lenisa Nina (Arquivos de Ciências do Mar, 2017)
This study presents the ecology of the ichthyofauna from Anil River estuary, regarding structure, diversity and species composition. Bimonthly captures were made from May/2000 and March/2002, using gill nets in four sites of the estuary. The similarity among the capture sites was analysed by Cluster Analysis, based on a presence-absence and relative abundance matrixes of the species, using the Square Euclidean Distance coefficient and Ward’s method (minimum variance) as clustering criterion. A total of 43 species belonging to 23 families and 35 genera were registered. Of this total, 12 species account for with less than 0.1% of the total number of sampled individuals and 15 accounted for less than 0.01% of total sampled weight. The community structure revealed Arius herzbergii, Mugil curema, Arius sp., Pseudauchenipterus nodosus and Mugil gaimardianus as the species with the highest percentage (87%) of specimens captured. Regarding the number of species, families Sciaenidae (12), Engraulididae (3) and Mugilidae (3) were the dominants. Values for diversity have showed low variability among the four sites sampled, indicating a homogeneous spatial distribution in this estuary showing expressive indexes in the months of May, 2001 and January, 2002, and lower on July, 2000 and March, 2002.